Estrategias de atención al cliente para el fortalecimiento del servicio en el departamento del centro de idiomas de la Universidad Técnica de Cotopaxi - Mosquera Bonilla, Jenny Marisol (2022)
The current research was made in the Language Center Departament from Cotopaxi Technical University, La Matrix campus, located at. Simón Rodríguez street, Latacunga Canton, Cotopaxi Province; its goal was to propose improvement strategies in the attention that received by Language Center departmen internal and external users from Cotopaxi Technical University, applying the quantitative methodology what consists of mathematical and statistical analysis for describing, explaining and predicting phenomena through numerical data, as well as a documentary-descriptive research, which allows getting a broad knowledge, regarding the topic, the same way, in the strategies and the análisis description and the attention type that offered the department. In the same way, it was made the data collection, through a questionnaire duly validated by experts, it composed 33 questions on a Likert scale, referring to study variables, such as customer service and service strengthening. For this research, it was applied the survey as a data collection technique, with a study population of 2,870 internal and external students; therefore, is was taken a sample 338 students from the Language Center. The got results indicated, what customer service according to the students criterio shows very favorable results. Regarding the perceptions, it can be observed, which the users expect to get the best attention from Language Center department staff, it is concluded, what the perspectives expected by the students are positive, it is important to take into account the given strategies: Listen the customer attentively and cordially, establishing a professional relationship with the customer, accompaniment and monitoring of user requests, providing new customer service channels, motivating the Language Center staff, establishing quality policies according to ISO standards; among others, what were already established in the given proposal, thus satisfactorily applying the proposed strategies, since its success depends on this.